The microRNA expression profiles in extracellular vesicles from HeLa cancer cells in response to cationic lipid- or polyethylenimine-mediated gene delivery. (2nd January 2019) - Lin, Chia-Wei; Jan, Ming-Shiou; Kuo, Jung-Hua Steven
Abstract: Intercellular communication is known to be involved in various stages of tumour development and metastasis through the secretion of extracellular vesicles (EVs) containing messengers such as microRNAs (miRNAs). Therefore, this study explored miRNA profiles in cancer cell-derived EVs after non-viral gene delivery in order to better understand the molecular information of intercellular communication in cancer cells after gene delivery. Two commonly used non-viral vectors (Lipofectamine 2000 and jet polyethylenimine) were used for the delivery of gene fluorescent protein plasmid in HeLa cancer cells. EVs were extracted and the contents of their RNA were subjected to the next-generation sequencing. In order to illustrate the common characteristics of non-viral vectors in the cancer cells, two overlapped up-regulated miRNAs (hsa-miR-143-3p and hsa-miR-193b-3p) were confirmed by real-time quantitative reverse transcriptase-polymerase chain reaction in the secreted EVs in response to both lipoplexes and polyplexes. The prediction of target genes and molecular pathways involved in these two miRNAs were determined, and the protein expressions related to the pathways of cell death and stress in HeLa cells were identified. Hsa-miR-143-3p and hsa-miR-193b-3p were found to be up-regulated by the use of different non-viral vectors and can thus serve as potential targets of non-viral cancer gene therapy.